Navigating the Digital Marketplace: The Dynamic Role of Social Media in Shaping Economic Trends (Journal of Universal Science Research, 2023)
Witness the rise of social media as a powerhouse shaping economic trends. With 4.2 billion users worldwide, these platforms have evolved into change agents, steering consumer behavior, reshaping markets, and predicting economic shifts. Explore their journey from personal networks to economic giants, democratizing advertising and enabling real-time adaptation. Uncover the sway of influencer culture on consumers and the potential of social media for economic analysis. Ethical concerns arise, but the future promises "social commerce" integrating shopping seamlessly and blockchain-driven transactions. As economies digitize, social media emerges as an indisputable force, revolutionizing global markets